2022
DOI: 10.1038/s41533-022-00281-z
|View full text |Cite
|
Sign up to set email alerts
|

Medication availability and economic barriers to adherence in asthma and COPD patients in low-resource settings

Abstract: Inhaled medication is essential to control asthma and COPD, but availability and proper adherence are challenges in low-middle income countries (LMIC). Data on medication availability and adherence in Central Asia are lacking. We aimed to investigate the availability of respiratory medication and the extent of financially driven non-adherence in patients with COPD and asthma in Kyrgyzstan. A cross-sectional study was conducted in two regions of Kyrgyzstan. Patients with a physician- and spirometry confirmed di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
2
12
0
1
Order By: Relevance
“…According to this review, only less than one-half of the participants were adherent to medications. Fragmented and fragile health care systems, inaccessibility, unavailability and unaffordability of drugs, 39 , 40 low socio-economic status of the African population, 41 and food insecurity and housing instability may be the reasons for the low prevalence of medication adherence among African adult asthmatic patients. 14 , 42 , 43 Evidence also showed that the prevalence of medication adherence is low in communities with inadequate health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…According to this review, only less than one-half of the participants were adherent to medications. Fragmented and fragile health care systems, inaccessibility, unavailability and unaffordability of drugs, 39 , 40 low socio-economic status of the African population, 41 and food insecurity and housing instability may be the reasons for the low prevalence of medication adherence among African adult asthmatic patients. 14 , 42 , 43 Evidence also showed that the prevalence of medication adherence is low in communities with inadequate health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Among 300 inhaler users, poor adherence to inhalers was noted among 81% with 68% reporting financial reasons as a barrier to proper inhaler adherence. 61 Illustrative of this finding, in 2007 1 month of maintenance asthma treatment from the private sector cost 1.3, 5.4, 2.5 and 2.3 days' wages for a lowest-paid government worker in Bangladesh, Nepal, Pakistan and Sri Lanka, respectively. 8 Limited budgetary allocations to preventive healthcare compared to the curative sector in many developing countries has led to poor availability of asthma diagnostics, medication, and support care, including spirometry services, allergic testing and asthma care nurses.…”
Section: Perceptions On Asthma Treatment Availability and Affordabilitymentioning
confidence: 98%
“…Underdeveloped national health services and limitations in free availability of asthma medications are major factors leading to treatment non‐adherence in many LMICs. Among 300 inhaler users, poor adherence to inhalers was noted among 81% with 68% reporting financial reasons as a barrier to proper inhaler adherence 61 . Illustrative of this finding, in 2007 1 month of maintenance asthma treatment from the private sector cost 1.3, 5.4, 2.5 and 2.3 days' wages for a lowest‐paid government worker in Bangladesh, Nepal, Pakistan and Sri Lanka, respectively 8 …”
Section: Challenges In Asthma Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In low-income and middle-income countries, both direct and indirect medical expenses attributable to COPD pose a serious threat to their economy 7–10. Hence, it is essential to motivate policy-makers and funders to provide political and financial support and encourage researchers to carry out relevant research for the prevention and control of COPD, especially in low-resource settings 11 12…”
Section: Introductionmentioning
confidence: 99%